Knowledge of Fraud and Taxpayer Compliance - Handoyo, Sigit; Candrapuspa, Hardhika Maghribi (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
Fraud is a unique crime committed by many people in various activities including in the tax sector that resulted in losses to the state. A research conducted in 2015 aimed at examining the factors that influence the taxpayer compliance in paying taxes with knowledge of fraud as a moderating variable. This research used Banguntapan city taxpayers as respondents. Sample collection method in this research used the convenience sampling method. The analytical tool used is Structural Equation Model (SEM) with the help of SmartPLS software. The results of this research prove that tax sanctions, service quality, and tax penalties have a positive effect on taxpayer compliance. The results of this research also prove that taxpayer knowledge does not positively affect the taxpayer compliance and also prove that the taxpayer interaction and knowledge of fraud have a positive effect on their tax paying compliance. So the implications of this research expect that tax authorities can apply tax laws in which including sanctions and taxes penalties evenly in each level of the taxpayers and improvement of services in the field of taxation in the form of provision of information to the taxpayers.Fraud is a unique crime committed by many people in various activities including in the tax sector that resulted in losses to the state. A research conducted in 2015 aimed at examining the factors that influence the taxpayer compliance in paying taxes with knowledge of fraud as a moderating variable. This research used Banguntapan city taxpayers as respondents. Sample collection method in this research used the convenience sampling method. The analytical tool used is Structural Equation Model (SEM) with the help of SmartPLS software. The results of this research prove that tax sanctions, service quality, and tax penalties have a positive effect on taxpayer compliance. The results of this research also prove that taxpayer knowledge does not positively affect the taxpayer compliance and also prove that the taxpayer interaction and knowledge of fraud have a positive effect on their tax paying compliance. So the implications of this research expect that tax authorities can apply tax laws in which including sanctions and taxes penalties evenly in each level of the taxpayers and improvement of services in the field of taxation in the form of provision of information to the taxpayers.